Effect of rehabilitation with or without noninvasive ventilation on pulmonary function and COPD assessment test results in COPD patients - Fakharian, Atefeh; Mobini Nejhad, Marzie; Kharabian Masouleh, Shahram; Abedi, Mohsen; Karimzadeh, Saba (Journal of Clinical Physiotherapy Research, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a serious and prevalent health condition, with many patients ultimately requiring ventilation support. Noninvasive ventilation (NIV) has been suggested as a therapeutic option for improving pulmonary function in these patients. This study aimed to evaluate the effectiveness of NIV for improving pulmonary function. Methods: Fifty hemodynamically stable patients with stage 3 or 4 COPD presenting to our center were randomly assigned into two groups of rehabilitation with (n=25) or without NIV (n=25). NIV was administered using I=12 and E=4 with BiPAP settings. Echocardiography, spirometry, six-minute walk test (6MWT), COPD Assessment Test (CAT), and venous blood gas (VBG) analysis were performed at baseline and after 4 weeks of rehabilitation and compared using appropriate statistical tests. Results: The mean age of the participants was 60.8±10.6 years and 84% were males. The two groups were similar regarding baseline variables, except for the higher number of stage 4 patients in the NIV group. The mean ejection fraction and pulmonary artery pressure were 53.6±4.3% and 37.2±9.6 mmHg, respectively, with no significant difference between the study groups (P>0.05). All pulmonary function indices by spirometry, 6MWT, and VBG values improved significantly after rehabilitation in each group (P<0.05), but NIV patients showed no advantage over the control group. However, NIV significantly increased the CAT scores after rehabilitation: 29.32 vs. 25.04, in the NIV and control groups, respectively (P<0.05). Conclusion: Despite having multiple health benefits in COPD patients including decreasing the mortality rate and the need for invasive ventilation, NIV showed superiority compared with rehabilitation alone only in improving the CAT score.